Traditional House of Lampung Kedatun Keagungan: Ethnomathematics Exploration - Noprisa Noprisa; Fitria Lestari; Desrina Hardianti; Dwi Desmayanasari; Suryatul Aini Asyhara; Deni Efendi; Dopy Rizko; Elsa Kurnia (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2024)
The purpose of this study is to explore Ethnomathematics of Geometry concepts in Kedatun Keagungan traditional house architecture. It is hoped that students will more easily explore understanding of mathematical abstractness through visual representations in familiar cultural forms. Learning mathematics by linking the surrounding culture so that learning is more meaningful for students. This research is a qualitative research with an ethnographic approach. Data collection techniques begin with observation, compiling and validating instruments, documentation studies and FGD. Data analysis technique uses the Spradley model. Based on the research results, it was found that Ethnomathematics in the Kedatun Keagungan traditional house has applied mathematical concepts both to the components of the house building and the ornaments inside which include: (1) the concept of geometry which consists of shapes, shapes and angles, (2) the concept of Geometry Transformations consisting of Symmetrical properties, Translation properties, Reflections, and Dilations. The results of this research can be used as a reference in developing teaching materials on Geometry material so that learning becomes more meaningful.